Aspek Manajemen Dalam Kegiatan Surveilans Epidemiologi Covid-19 Di Puskesmas Dharmarini Kabupaten Temanggung - Annisa Nida Sakina; Chriswardani Suryawati; Eka Yunila Fatmasari (Jurnal Manajemen Kesehatan Indonesia, 2021)
Dharmarini Public Health Center has a high number of COVID-19 cases and there are COVID-19 epidemiological surveillance activities that are not in accordance with those stated in the guidelines, specifically in health monitoring and in terms of Community-Based Surveillance that vulnerable populations have not been recorded and reported. Based on a preliminary study, Dharmarini Public Health Center only has a surveillance officer and experienced obstacle in cross-sectoral coordination. This study aims to analyze the management aspects of COVID-19 epidemiological surveillance at Dharmarini Public Health Center include planning, organizing, actuating, and controlling. This is a qualitative research with analytical descriptive approach. Primary data collection was done by in-depth interviews and research subjects were selected by purposive sampling. The result shows that management aspects in COVID-19 epidemiological surveillance activities at Dharmarini Public Health Center have been carried out from planning, organizing, actuating, to controlling, but there are still shortcomings including in actuating that not all officers involved have received training, there is obstacle in cross-sectoral coordination, the implementation of health monitoring can still be improved, there are refusals in tracing, Community Based Surveillance has not been fully implemented, supervision has only been held once, and in controlling aspect that the evaluation carried out is still not comprehensive. Dharmarini Public Health Center is suggested to optimize the actuating and controlling aspects in COVID-19 epidemiological surveillance.